Analysis of Lightning Interference on The 500 Kv Depok-Tasik Transmission Tower - Wulandari, Rindi (Journal of Green Science and Technology, 2023)
Lightning is a natural phenomenon that can cause damage to transmission lines and cause disturbances in the distribution of electrical energy. Indonesia is a country with a high density of lightning strike in tropical areas such as in Java Island (Indonesia). The 500 kV Depok-Tasik transmission tower is part of the West Java interconnection. This transmission is 142 kms away and is supported by a tower of 340 units (tower 326-666), this transmission uses dual channels. This study aims to analyze and determine the method of lightning protection and to determine the magnitude of the voltage arising from a lightning strike in the 500kV transmission tower Depok-Tasik in order to be able to see the transmission parameters of the lightning density map, the trend of the time of the strike and the peak current frequency of the overvoltage caused by the lightning strike by analyzed using software falls. Software falls is a lightning analysis software used to study the relationship between lightning events and geographically referenced assets. Anomaly data on the 500kV Depok-Tasik conductor in 2021-2022 occurred 12 times, disturbances occurred 6 times in 2021 and 6 disturbances occurred in 2022, this can be a reference for asset inventory in the future.